Gypsum Addition in Moulding Sand to Manufacture Defect Free Tin Castings - T.R. Vijayaram (International Journal of Fracture Mechanics and Damage Science, 2024)
Sand molding is a versatile casting process that provides freedom of design with respect to size, shape, and product quality. Plaster casting is similar to sand molding process except that a plaster is substituted instead of sand. Plaster compound is composed of gypsum, which strengthens the mould. Parts made by this process are gears, valves, fittings, tooling, and ornaments. The finished product of plaster casting has a very high surface finish and fine tolerances can be attained. Gypsum in the plaster will slowly reacts with the iron and the maximum temperature of plaster casting is limited to 1200 degree centigrade, which limits the material to be cast by using this method. A thin layer of parting film is usually sprayed to the pattern to prevent mold from sticking the pattern, and this step is a necessary one. In this method, the mold box is shaked to allow the filling of the sand in the cavities around the pattern, and it is then dried at the temperature between 120 degree centigrade to 260 degree centigrade. In this research work, a simple shape of anvil is used as the mould cavity when performing sand casting process. The molten metal used is tin and tin castings are processed. The effect of gypsum addition in moulding sand is studied and surface finish of the casting is revealed and observed before and after gypsum addition. Besides, microstructure of casting is analyzed after and before addition of gypsum in the moulding sand.
Keywords: Gypsum; green sand moulding; moulding sand; surface defects; surface finish